The role of online platforms in weathering the COVID-19 shock (OECD Policy Responses to Coronavirus (COVID-19), 2021)
This policy brief reports on the activity of online platforms during the COVID-19 crisis. Google Trends data for OECD and other G20 countries indicate that in some areas (such as retail sales, restaurant delivery, and mobile payments) online-platform use increased markedly during the first half of 2020, when most countries imposed lockdown and physical distancing measures. Thus, in this period, some economic transactions may have shifted to online marketplaces as people and businesses increasingly turned to online platforms to pursue economic and social activities. The rise in platform use was however highly heterogeneous across areas of activity and countries. Countries with higher levels of economic and technological development, easier access to infrastructure and connectivity, better digital skills, and wider Internet use tended to experience a larger increase in the use of online marketplaces, possibly mitigating the negative effects on output and jobs of the COVID-19 shock. This highlights the role of policies in strengthening countries' digital preparedness and their resilience to future shocks